Praktik Akad Pembiayaan Nasabah Studi: Analisis Penetapan Akad Pembiayaan Nasabah di Bank Syariah Indonesia (BSI) Surakarta - Suryono, Joko (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This research was carried out at Bank Syariah Indonesia (BSI) Surakarta, with the aim of finding out whether the implementation of murabahah contract financing is in accordance with Islamic principles and whether it is in accordance with the fatwa that has been determined by the DSN-MUI. This research method uses interviews, observation and documentation. This research uses qualitative descriptive analysis. The results of this research can be concluded that the implementation of murabahah financing at Bank Syariah Indonesia Surakarta uses a tiered percentage system each year from the principal of its murabahah financing. Margin determination is still based on the BI Rate and looking at the margins applicable at other banks. The system for implementing murabahah financing at banks can start from administrative requirements, collateral requirements, financing terms, financing ceiling, financing period, and fees charged to customers. In determining the murabahah financing margin, the annual inflation rate is still used. So the higher the BI rate, the higher the margin taken by the bank from its customers.